2007
DOI: 10.1007/s12034-007-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and ion exchange properties of zirconium(IV) tungstoiodophosphate, a new cation exchanger

Abstract: Zirconium(IV) tungstoiodophosphate has been synthesized under a variety of conditions. The most chemically and thermally stable sample is prepared by adding a mixture of aqueous solutions of 0⋅5 mol L -1 sodium tungstate, potassium iodate and 1 mol L -1 orthophosphoric acid to aqueous solution of 0⋅1 mol L -1 zirconium(IV) oxychloride. Its ion exchange capacity for Na + and K + was found to be 2⋅20 and 2⋅35 meq g -1 dry exchanger, respectively. The material has been characterized on the basis of chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The effect of temperature on the removal of Th(IV), Eu(III), Sm(II), and Fe(III) in aqueous solution by synthetic analogue of heulandite was studied by varying the temperature between 303-323 K. The data presented in Fig. 9 showed that sorption of metal ion by the synthetic analogue of heulandite increased with increase in temperature, which is generally expected for the sorption/ion exchange of most metal ions from their solution [70][71][72][73][74][75][76][77][78][79]. However, the magnitude of such increase continues to decline at higher initial metal ions concentration, as temperatures are increased from 303 to 323 K. This is because with increasing temperature, the attractive forces between sorbent surface and metal ions are weakened and the sorption decreases.…”
Section: Effect Of Initial Metal Ion Concentration and Temperature Ofmentioning
confidence: 92%
“…The effect of temperature on the removal of Th(IV), Eu(III), Sm(II), and Fe(III) in aqueous solution by synthetic analogue of heulandite was studied by varying the temperature between 303-323 K. The data presented in Fig. 9 showed that sorption of metal ion by the synthetic analogue of heulandite increased with increase in temperature, which is generally expected for the sorption/ion exchange of most metal ions from their solution [70][71][72][73][74][75][76][77][78][79]. However, the magnitude of such increase continues to decline at higher initial metal ions concentration, as temperatures are increased from 303 to 323 K. This is because with increasing temperature, the attractive forces between sorbent surface and metal ions are weakened and the sorption decreases.…”
Section: Effect Of Initial Metal Ion Concentration and Temperature Ofmentioning
confidence: 92%
“…compounds containing two different cations and a given anion or two different anions and a cation, are interesting since they exhibit improved properties in comparison to their single salt counterparts [32,33]. Mixed materials have been widely investigated and exhibit improved ion exchange characteristics compared to their single salt counterparts [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium based ion exchangers have received attention because of their excellent ion-exchange behaviour and some important chemical applications in the field of ion exchange, ion-exchange membrane, and solid state electrochemistry [18]. Goward et al [19] have reported that polyaniline Zr(IV) tungstophosphate nanocomposite ion exchanger was used for the selective separation of Pb 2+ . The literature reveals that several three-component ion exchangers, that is, zirconium(IV)iodooxalate, zirconium(IV)phosphosilicate, zirconium (IV) phosphoborate, and zirconium(IV)tungstophosphate [20], behaviour studied for their synthesis, ionexchange behavior, and analytical applications.…”
Section: Author: Meraj Alam Khanmentioning
confidence: 99%